Limb Shortening in Femoral Shaft Fractures Treated by Early Spica Cast in Children - Yasir Hussain, Saeed Ahmed Shaikh, Zahoor Ellahi Soomro, Badaruddin Sahito, Qasim Samejo, Arif (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the frequency of limb shortening in diaphyseal femur fractures in children treated by early spica cast. Methods: This cross-sectional study was conducted at the department of Orthopedics, Jinnah Postgraduate medical centre, Karachi. 100 children with femur fracture were enroled in the study by non probability consecutive sampling. The inclusion criteria were patients having shaft fractures within a week duration, aged between 1 to 08 years of either gender. Results: Mean age of the patients was 4.25 ± 2.29 years. Boys were predominantly higher (68%) as compared to girls (32%). Mean limb length at cast removal was 1.39 ± 0.62 cm. Frequency of limb shortening was found in 35% patients only. Conclusion: In early age due to compensatory overgrowth and potential of remodeling process, early Hip Spica Cast technique is a safe, attractive and cost-effective method and provides excellent results in terms of union and shortening.